Emerging role of cardiac computed tomography in heart failure. (10th August 2019) - Aziz, Waqar; Claridge, Simon; Ntalas, Ioannis; Gould, Justin; de Vecchi, Adelaide; Razeghi, Orod; Toth, Daniel; Mountney, Peter; Preston, Rebecca; Rinaldi, Christopher A.; Razavi, Reza; Niederer, Steven; et al.
Abstract: Despite medical advancements, the prognosis of patients with heart failure remains poor. While echocardiography and cardiac magnetic resonance imaging remain at the forefront of diagnosing and monitoring patients with heart failure, cardiac computed tomography (CT) has largely been considered to have a limited role. With the advancements in scanner design, technology, and computer processing power, cardiac CT is now emerging as a valuable adjunct to clinicians managing patients with heart failure. In the current manuscript, we review the current applications of cardiac CT to patients with heart failure and also the emerging areas of research where its clinical utility is likely to extend into the realm of treatment, procedural planning, and advanced heart failure therapy implementation.